2003
DOI: 10.4161/cbt.204
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Promoter-Driven Cancer Cell Suicide

Abstract: Human telomerase is highly active in more than 85% of primary cancers, regardless of their tissue origins, but not in most differentiated somatic tissues. Because of this, telomerase recently has become a popular target of anticancer therapy and has been used as a marker of cancer. Similarly, telomerase promoters, especially telomerase reverse transcriptase (TERT) promoter, have been zealously tested for targeted cancer gene therapy. In vitro and in vivo studies have demonstrated that the human TERT (hTERT) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 44 publications
1
48
0
2
Order By: Relevance
“…The human telomerase promoter has been used successfully for this purpose (41). For breast cancer, estrogen and hypoxia-responsive promoters have been used to drive the expression of E1A (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…The human telomerase promoter has been used successfully for this purpose (41). For breast cancer, estrogen and hypoxia-responsive promoters have been used to drive the expression of E1A (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies used the hTERT promoter to drive antitumor gene expression selectively in cancer cells without or little affecting normal cells or tissues. [24][25][26] For example, one study reported that the hTERT promotor can drive the TRAIL gene to suppress pancreatic tumor cell growth, preventing possible liver toxicity of the TRAIL gene. 27 The SG300 gene driven by the hTERT promoter expressed selectively in cancer cells resulted in apoptosis and necrosis of cancer cells without effects on normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…65,66 and, furthermore, more amenable to a second layer of tumor specificity via tumor-targeted vector control thereby minimizing nonmalignant cell uptake and potential toxic effect to nontarget agents. [67][68][69][70][71][72] Comparing patient-specific molecular profiles with known pathways and with networks derived from protein interaction databases provides a means for identifying oncotoxic targets. However, the majority of the data underlying our understanding of cancer and, especially, the characterization of cancer gene-protein-metabolic networks, are based on animal and cell line systems.…”
Section: Discussionmentioning
confidence: 99%